Temperature Control System in Closed House for Broilers Based on ANFIS - Alimuddin Alimuddin; Kudang Boro Seminar; I Dewa Made Subrata; Nakao Nomura; Sumiati Sumiati (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Indonesia is a tropical country with high ambient temperatures for broilers since daily temperature reaches an average daily temperature of 360C (maximum) and 320 C (minimum); whereas the optiml temperature for broilers is in the range of 28-300C. Thefefore, midle or large scale broiler industries have been using a control system to maintain the optimal temperature within a broiler house. Therefore, the role of a control system for regulating environmental parameters, not only temperature but also humidity, light intensity, and amonia content level, is very critical and relevant for better broiler production. This study aims to design an ANFIS control system for controlling the temperature inside a broiler house (closed house) for broiler. Data is collected at three different periods of the starter period (5 days): 29.50C-30.900C, a period of 25 days is a grower-29.0C 34.20C, and the finisher of 30 days is obtained 33.20C. Set point control simulation using the same temperature 290C for starter, grower and finisher period. The simulation results show the output in a closed house temperature fluctuates around set point the 290C-340C.